Evaluation of ecosystem services linked to the water resource of the glaciers of the Olivares-Colorado basins, Andes of Central Chile - Rocha, Alexis Segovia; Casassa Rogazinski, Gino (My University, 2025)
An assessment of the ecosystem services of water storage and continuous water supply was carried out in the Olivares and Colorado River basins, Maipo River basin, Metropolitan Region, Chile. To carry out the assessment of the ecosystem service of water stor-age, the indirect market method "avoided cost" was used, and to estimate the value of continuous water supply, a direct market valuation was used. The results showed that the Olivares-Colorado basins together contain 29.2% of glaciers, 46.2% of the ice surface and 55.7% of the water in the form of ice in the Maipo River basin. The sum of both ecosystem service values for both basins resulted in an annual value of USD 902 million, and a projected present value of USD 14,224 million over 50 years. This annual value exceeds by 32 times the budget for the entire National System of State Protected Wild Areas (SNASPE) for the year 2022, so its high associated value amply justifies the protection of these glaciers.
Valoración de servicios ecosistémicos vinculados al recurso hídrico de los glaciares de las cuencas Olivares-Colorado, Andes de Chile Central
Keywords: ecosystem services; glacier; national park; water supply